2013
DOI: 10.1097/hjh.0b013e32835f749c
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise training increases neuronal nitric oxide release and bioavailability and decreases noradrenaline release in mesenteric artery from spontaneously hypertensive rats

Abstract: Aerobic exercise training decreases contractile response to EFS in mesenteric artery from SHRs. This effect is the net result of decreased noradrenaline release, increased sensitivity to the vasoconstrictive effects of noradrenaline and increased neuronal nitric oxide release and bioavailability. These modifications might contribute to the beneficial effects of aerobic exercise training on blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…Several studies have reported that plasma levels of NO Å metabolites, nitrite and nitrosothiols increase during exercise in both rodents and humans (Blanco-Rivero et al, 2013;Calvert, 2011;Kimura et al, 2003;Linke et al, 2008). More recently, Calvert and co-workers showed that sustained cardioprotective effects of 4 weeks of voluntary exercise are mediated by increased phosphorylation of cardiac eNOS ser1177 , leading to an increase in NO Å generation and storage of NO Å metabolites (i.e.…”
Section: Ischemia-reperfusion Injurymentioning
confidence: 96%
See 2 more Smart Citations
“…Several studies have reported that plasma levels of NO Å metabolites, nitrite and nitrosothiols increase during exercise in both rodents and humans (Blanco-Rivero et al, 2013;Calvert, 2011;Kimura et al, 2003;Linke et al, 2008). More recently, Calvert and co-workers showed that sustained cardioprotective effects of 4 weeks of voluntary exercise are mediated by increased phosphorylation of cardiac eNOS ser1177 , leading to an increase in NO Å generation and storage of NO Å metabolites (i.e.…”
Section: Ischemia-reperfusion Injurymentioning
confidence: 96%
“…Of interest, a single bout of either aerobic or resistance exercise increases endothelial-dependent relaxation through NO Å pathways (Faria Tde et al, 2010;Yang et al, 2010). Moreover, improved NOS activity and diminished ROS production have been associated with better vascular function in hypertensive rats submitted to either moderate-or high-intensity aerobic exercise training (Blanco-Rivero et al, 2013;Kimura et al, 2010;Roque et al, 2013a,b;Yang et al, 2011). The use of either ROS scavenger or NOS inhibitor abolishes the improvement of endothelial function mediated by exercise training in coronary arterioles from pigs (Xie et al, 2012).…”
Section: Hypertensionmentioning
confidence: 97%
See 1 more Smart Citation
“…For this purpose, in the present study, two different vessels were used, mesenteric and tail arteries, which have been extensively used as models for the study of neuromodulation exerted by many substances in the vasculature [5,7,8,3133] and where we have previously described the presence of adenosine receptors on sympathetic nerves [24,27]. …”
Section: Introductionmentioning
confidence: 99%
“…9-11 Recently, our group have showed that acute resistance exercise induce an intensity-dependent effect on NO synthesis and vascular relaxation in mesenteric arteries of healthy rats. 12,13 The mesenteric artery regulates 20% of the blood flow and effectively participates in the total peripheral resistance, and thus, is directly involved in vascular changes promoted by exercise.…”
Section: Introductionmentioning
confidence: 99%